2016
DOI: 10.1186/s12862-016-0830-x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of functional divergence in MSP7 paralogous proteins: a molecular-evolutionary and phylogenetic analysis

Abstract: BackgroundThe merozoite surface protein 7 (MSP7) is a Plasmodium protein which is involved in parasite invasion; the gene encoding it belongs to a multigene family. It has been proposed that MSP7 paralogues seem to be functionally redundant; however, recent experiments have suggested that they could have different roles.ResultsThe msp7 multigene family has been described in newly available Plasmodium genomes; phylogenetic relationships were established in 12 species by using different molecular evolutionary ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 76 publications
1
7
0
Order By: Relevance
“…A percentage of sites under positive selection were identified in P. vivax and other species regarding the aBSREL method ( Figure 2A ). This pattern has also been observed in other genes, suggesting species-specific adaptation during parasite evolution ( Muehlenbein et al, 2015 ; Buitrago et al, 2016 ; Garzon-Ospina et al, 2016 ). Evidence of positive selection was found in PvRBSA-B ( Figure 2 and Tables 3 , 4 ), agreeing with the frequency spectrum-based test results.…”
Section: Discussionsupporting
confidence: 70%
“…A percentage of sites under positive selection were identified in P. vivax and other species regarding the aBSREL method ( Figure 2A ). This pattern has also been observed in other genes, suggesting species-specific adaptation during parasite evolution ( Muehlenbein et al, 2015 ; Buitrago et al, 2016 ; Garzon-Ospina et al, 2016 ). Evidence of positive selection was found in PvRBSA-B ( Figure 2 and Tables 3 , 4 ), agreeing with the frequency spectrum-based test results.…”
Section: Discussionsupporting
confidence: 70%
“…Evidence of episodic positive selection was found in some parasite lineages (Additional file 2 : Figure S2). As shown for other antigens [ 49 51 ], the episodic selection found in GAMA could be the outcome of adaptation to different hosts during malaria-primate evolution [ 50 , 51 ]. Therefore, the insertions found in P. vivax could be an adaptation of the species to humans since the RR in malaria are associated with evasion of the host’s immune response, making such response become directed against functionally unimportant regions [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the diversity of msp 7 within species, finding that msp7 -A paralogs are well conserved within species ( Castillo et al, 2017 ), a finding well supported here ( Figure 4 ). The differences in redundancy and interspecies conservation have previously been suggested to correspond to different roles in invasion for msp7 subtypes A, B and C ( Garzon-Ospina et al, 2016 ). Patterns of variation within the MSP7-B subfamily closely mimic whole genome findings, suggesting MSP7-B is a viable measure of population diversity ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 96%